Системная трансформация посткоммунистических стран Центральной и Восточной Европы: российские и украинские исследования в ХХI ст. - Брусиловская, Ольга (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2019)
The research topic follows, firstly, from the fact that there is a need to examine the scientific schools of the 21st century. Secondly, the general tendency towards the re-ideologization of political science requires a critical interpretation of the state of affairs in the Russian Federation and Ukraine. Thirdly, in Ukraine and in the countries that are its allies, the theoretical analysis of historiography should be particularly helpful in offering a more clear definition of the former and current ideological positions of the aggressor country (the Russian Federation). The article compares the Russian and Ukrainian schools of political science, which have explored the impact on CEE of such actors as the EU, NATO, the USA, and Germany, as well as the economic, political, and ideological components of the systemic transformation.